qnrA prevalence in extended-spectrum β-lactamase-positive enterobacteriaceae isolates from Turkey - (:unkn) unknown (My University, 2008)
Quinolone resistance mostly originates from chromosomal mutations. In recent years, however, plasmid-mediated quinolone resistance has been reported in several parts of the world. Plasmid-borne qnrA, qnrB, or qnrS genes are responsible for this kind of resistance. Little is known about the diversity, type, and species range of the qnr genes in Turkey. We screened qnrA, qnrB, and qnrS genes in quinolone-resistant blood culture isolates collected from six different medical centers in Turkey which produced extended-spectrum β-lactamases (ESBLs). Atotal of 78 ESBL-positive isolates were enrolled in this study. Of these, 37 (47.4%) were nalidixic-acid resistant or intermediate. qnrA was found on large plasmids isolated from five (6.4%) of the NalI/R isolates. In three of these, the same plasmid also carried blacCTX-M. Four of the qnrA-positive isolates were Klebsiella pneumoniae from Dokuz Eylul University Hospital, Izmir, and the fifth isolate was Escherichia coli from Istanbul University Hospital. Two of the isolates from Izmir were found by enterobacterial repetitive intergenic consensus sequpnce-PCR to be clonally related, This is the first report on the qnrA prevalence among ESBL-positive blood culture isolates collected from different regions in Turkey. According to our results, plasmid-mediated resistance is a potential problem for the spread of quinolone resistance, and this mechanism could be emerging strongly among the ESBL-positive Enterobacteriaceae in Turkey.